Primary Chordoma of the Nasopharynx: A Rare Case Report and Review of the Literatures - Ery Kus Dwianingsih; Yosinta Snak; Hanggoro Tri Rinonce; Brian Wasita; Ester Lianawati Antoro; Samir S. Amr (Hindawi Limited, 2019)
Primary chordoma of the nasopharynx is an extremely rare malignant tumor of notochordal origin in the extra-osseous axial skeleton. It presents as a soft tissue mass without involvement of the skull base bone (clivus) and may mimic other lesions of the nasopharynx. A 26-year-old male patient is presented with nasal obstruction and congestion for the last 3 years. Physical and radiological examination revealed a mass in the naso-oropharyngeal region. It was suspected to be a cystic mass or abscess on radiological imaging. However, histopathological examination revealed a chordoma. We review all 20 cases of primary nasopharyngeal chordoma reported previously in the literature. Nasopharyngeal chordoma should be considered in the differential diagnosis of nasopharyngeal mass due to its unspecific appearance on clinical and radiology examination.